STYLE, CONTEXT AND TRANSLATED NARRATIVES: A SOCIO-SEMIOTIC PROFILE FOR STUDYING STYLE IN TRANSLATED NARRATIVES - Aljahdali, Sawsan A. (Indonesian Journal of Applied Linguistics, 2017)
A translated narrative has both its structure and texture creatively reproduced in the decoding-reencoding processes. These processes of intersemiotic and interlingual transformations yield variable results influenced by language-in-context, as the broadest environment of translation, and prompted by the level of the typological and semiotic distance between texts. Translation is thus an act of communication that is separate (contextually and discursively) from, while it is still dependent (semantically) on, the original writing. Here, the translatorâ€™s style is an â€œimprintâ€ that is simultaneously compelled by the creativity of the literary translation act and the existence of the targeted reader in a new socio-semiotic context (Baker, 2000; Hasan, 1986/2011, 1989; Hatim Mason, 1997; MalmkjÃ¦r, 2004; Matthiessen, 2001). In response to Baker (2000), the present study aims to theoretically revisit the issue of style in narrative translation in a comparative view that takes into consideration the multiple contexts and meta-contexts of the acts of creation and translation. This comparative intersemiotic view ventures to address the complexity of narrative meaning recreation in these new acts of communication along the multi-stratal systems of language and narrative and in the light of the narrative, stylistic and socio-semiotic views of discourse and meaning.